2011
DOI: 10.1021/jp200845e
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organo–Inorganic Clay with Nonionic Interlayers. Mid- and Near-IR Spectroscopic Studies

Abstract: The intercalation of organic polymers molecules (i.e., PEGs and BRIJ) into a standard Ca-montmorillonite has been studied by XRD, TG, and IR spectroscopy. The polymer intercalation is confirmed by the increasing of the d(001) in XRD spectra as well as by the complex multisteps thermal decomposition behavior of the organo-clay materials. Mid-IR and diffuse reflectance near-IR spectra of the intercalated materials show the polymer diagnostic bands (CH stretching and deformation mode), shifted or changed in shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 37 publications
6
59
0
Order By: Relevance
“…Moreover, this result ensured that the KC was only performed as a gelling agent without intercalating into nanoclay galleries in order to maintain the PEG‐intercalated clay within the gel formation. In other words, the creation of the PEG organo–inorganic hybrid compounds is displayed . The same results have been reported in many research studies based on the intercalated PEG/Clay nanocomposites (Zampori et al , Finocchio et al , Campbell et al , and Clegg et al ).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, this result ensured that the KC was only performed as a gelling agent without intercalating into nanoclay galleries in order to maintain the PEG‐intercalated clay within the gel formation. In other words, the creation of the PEG organo–inorganic hybrid compounds is displayed . The same results have been reported in many research studies based on the intercalated PEG/Clay nanocomposites (Zampori et al , Finocchio et al , Campbell et al , and Clegg et al ).…”
Section: Resultssupporting
confidence: 80%
“…In other words, the creation of the PEG organo–inorganic hybrid compounds is displayed . The same results have been reported in many research studies based on the intercalated PEG/Clay nanocomposites (Zampori et al , Finocchio et al , Campbell et al , and Clegg et al ). The slight enlargement of the basal spacing was observed with increasing PEG contents indicating that the minor enthalpy interactions were affected by increasing the PEG loading.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, the enthalpic driving force occurred from the interactions from the hydrogen bonding between the hydroxyl and ether oxygen groups of PEG, water molecules, and Si-O-Si on the clay surfaces [12,50]. Numerous studies have reported similar results based on the intercalated PEG/clay nanocomposites, such as Zampori et al [30], Finocchio et al [31], Clegg et al [50], and Campbell et al [36]. is result could be attributed to the organophilicity of the achieved nanoclay aerogel masterbatches, which was enhanced from this process that resembled the typical surface modification of the organoclay preparation.…”
Section: Part 1: Preparation Of the Nanoclay Aerogel Masterbatchmentioning
confidence: 91%
“…Moreover, PEG-treated nanoclay is thermally stable at 327°C in an inert atmosphere and 275°C in air, which is greater than alkylammonium salts; therefore, it could be processed at a higher temperature without thermal degradation than typical organoclay [17,29]. According to the reports of Zampori et al [30], Finocchio et al [31], and Belova et al [32], PEG with the MW of 1500 (PEG1500) was used as a nonionic surfactant to prepare the organoclays. e PEG-intercalated clay had the ability to modify the clay's surface to be organophilic due to the interaction between the oxygen atoms of the PEG molecule and sodium cations dwelling in the interlayers of the layered silicate and between the PEG molecule and nanoclay surface via hydrogen bonding; hence, the long tails of the PEG molecular chain were able to interact with the organic polymer [12,15,33,34].…”
Section: Introductionmentioning
confidence: 99%